2018
DOI: 10.3390/ijms19103014
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Immunohistochemical Markers with Prognostic and Predictive Significance in Liver Metastases from Colorectal Carcinoma

Abstract: Despite the significant recent achievements in the diagnosis and treatment of colorectal cancer (CRC), the prognosis of these patients has currently plateaued. During the past few years, the opportunity to consider multiple treatment modalities (including surgery and other locoregional treatments, systemic therapy, and targeted therapy) led to the research of novel prognostic and predictive biomarkers in CRC liver metastases (CRCLM) patients. In this review, we seek to describe the current state of knowledge o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 107 publications
0
13
0
1
Order By: Relevance
“…More data are available from expression-profiling analyses of clinical samples and/or animal models with CRC liver metastasis. In these studies, various gene signatures for colon-to-liver metastasis were suggested [ 131 , 132 ]. Although many identified signatures or molecular markers have been validated by other groups, yet none of them has been used as a diagnostic or prognostic tool applicable to clinical practice as reviewed [ 133 , 134 ].…”
Section: Experience In Predicting Markersmentioning
confidence: 99%
“…More data are available from expression-profiling analyses of clinical samples and/or animal models with CRC liver metastasis. In these studies, various gene signatures for colon-to-liver metastasis were suggested [ 131 , 132 ]. Although many identified signatures or molecular markers have been validated by other groups, yet none of them has been used as a diagnostic or prognostic tool applicable to clinical practice as reviewed [ 133 , 134 ].…”
Section: Experience In Predicting Markersmentioning
confidence: 99%
“…Colorectal adenoma-carcinoma sequence observed in most of the CRC cases in humans (CIN tumors, 84%) is associated with high frequency of DNA somatic copy number alterations (SCNA), with common mutations in APC , TP53 , KRAS , SMAD4 , and PIK3CA [7,10,18,19,20]. On the other hand, serrated neoplastic pathways associated with BRAF mutations, hMLH1 promoter hypermethylation, as well as MSI constitute 14–30% of CRC cases [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…A modulating influence of genetic variants of IGF2 receptor ( IGF2R) ( IGF2R c.5002 G > A and IGF2R c.901 C > G variants) on higher circulating IGF2 levels was also proven [59]. Based on TCGA data, it was proven that, among mutated genes typical for CRC (e.g., APC, TP53, SMAD4, PIK3CA , and KRAS ) [5,19,20], there were also copy-number changes including amplifications of ERBB2 and IGF2 [6,29]. Recent data also describes the CRIS-D subtype, which includes Wingless/Integrated (WNT) pathway activation as well as IGF2 overexpression and amplification.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular alterations can be used for diagnostic [1], prognostic [2,3,4,5,6,7] and predictive [7] purposes. Furthermore, the use of bioinformatics and machine learning could help to define and validate novel “omics-based” markers with important diagnostic and prognostic implications [1].…”
mentioning
confidence: 99%
“…miRNAs are released into exosomes, a process thought to mediate liver metastasis through the preparation of the pre-metastatic niche [10]. Although several other biomarkers have been linked to liver metastasis, none have provided sufficiently robust results to confirm their involvement [7]. Long non-coding RNAs (lncRNAs) also play an important role in different biological processes involved in cancer.…”
mentioning
confidence: 99%